THE DEVELOPMENT OF MULTIMEDIA-BASED TEACHING MATERIALS IN THE CIVIL LAW COURSEWORK - Kurnisar, Kurnisar; Artati, Sri; Fatihah, Husnul; Nurdiansyah, Edwin (Universitas Pendidikan Indonesia, 2018)
This study aims to develop multimedia-based teaching materials in the lectures of Civil Law/Trade. This research uses ADDIE Model (Analyze, Design, Development, Implementation, and Evaluation Model) and the data is analyzed quantitatively. The subjects of the study are students who taking the Civil/Trade Law Coursework in odd semester 2017-2018. Based on the results, it can be concluded that the multimedia-based teaching materials that developed this valid, practical and potential effect in improving students' understanding of the subject of civil law / trade law with the assessment of 82.5% of media expert validation.